Nurses in Public Health: A profession in continuous evolution - Teresa Rea; Maria Rosaria Esposito; Assunta Guillari; Silvio Simeone; Gianpaolo Gargiulo; Grazia Isabella Continisio; Nicola Serra (Epidemiology, Biostatistics and Public Health)
Today, nurses play a fundamental role in Public Health. In the last few decades the health profession has seen strong professional growth, in the areas of Clinical practice, Management and Education. In particular, this growth has been also informed by the progress being made in nursing research. In fact, nursing research has contributed to the establishment of support tools to facilitate and evaluate the daily work done by nurses, contributing significantly to the improvement of their professional performance.